Perceived Correctional Environment and Aggression on Violent Behaviors among Inmates in Rivers State - Enyelunekpo E. Roberts; Oluwunmi A. Obisesan; Gift J. John; Emmanuel E.Uye (Jurnal Ilmu Sosial dan Humaniora, 2025)
Violence behavior among inmates in correctional facilities is a significant problem in many countries around the world. Studies linking perceived correctional environment and aggression on violent behavior among inmates tend to be lacking. Therefore, this study examines the predictive role of perceived correctional environment and aggression on violent behavior among inmates in correctional facilities in Rivers State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select one correctional facility in Rivers State. A convenience sampling method was used to collect data from 223 inmates using validated questionnaires and analyzed using multiple regression statistics to test one hypothesis which was accepted at p